Mogućnosti racionalizacije poslovanja cestovnoga transportnog poduzeća - Rajsman, Marijan (Promet - Traffic&Transportation, 2012)
This paper deals with identifying the existing state of affairs and possibilities for restructuring of a medium operator with the objectives of higher efficiency and optimum operations. The author advocates the concept of having the basic approach to such restructuring governed by the functional principle within the scope of the registered business of the company. The paper further deals with the present level of engagement of the company as well as the trend of business indices on completed transport services as compared with the last fiscal year. A technical and utilization analysis of transport capacities in passenger and freight transport has been completed with particular reference to the issues of maintenance and reliability of the motor pool placing accent on to the need for the introduction of a programmed preventive maintenance of vehicles. Particular attention has been paid to the services/ /garage division whose operations primarily viewed from the aspect of prevention measures should considerably contribute to the higher level of optimum operational aspect of the motor pool. The existing management chart of the urban and suburban transport has been committed to analysis.